Feasibility and acceptability of introducing routine antenatal contraceptive counselling and provision of contraception after delivery: the APPLES pilot evaluation. (19th May 2017) - Cameron, ST; Craig, A; Sim, J; Gallimore, A; Cowan, S; Dundas, K; Heller, R; Milne, D; Lakha, F
Abstract : Objective: To determine the feasibility and acceptability of routine antenatal contraceptive counselling and contraception provision including long‐acting reversible contraception (LARC) postpartum. Design: Health service research evaluation. Setting: Community antenatal clinics and hospital maternity settings in National Health Service, Scotland UK. Population: Women booked for antenatal care. Methods: Contraceptive counselling with a community midwife (22 weeks' gestation) and provision of contraception (with facilitated access to LARC methods) prior to discharge from maternity hospital. Evaluation consisted of (i) self administered questionnaire (32–34 weeks) of women's views of antenatal contraceptive counselling, (ii) database review of contraceptive methods provided at discharge, and (iii) focus groups with midwives and obstetricians. Main outcome measures: Women's views on antenatal contraceptive counselling. Secondary outcomes included (i) uptake of LARC methods and (ii) barriers and facilitators to providing antenatal counselling and contraception. Results: There were 1369 women in the cohort. Questionnaires were distributed to 1064 women (78%) and completed by 794 (75%). In all, 78% of respondents ( n = 621) discussed contraception antenatally with a community midwife and 74% ( n = 461) found this helpful. Although 43% of respondents ( n = 341) were planning to use LARC, only 9% of the cohort (118 of 1369) received LARC prior to discharge. Community midwives indicated that antenatal contraceptive counselling was now embedded in their role, but hospital staff indicated that workloads impacted upon ability to provide contraception for women. Conclusions: Antenatal contraceptive counselling, delivered by community midwives, is feasible and highly acceptable to women. However, providing contraception and LARC for women before they are discharged home remains a challenge. Tweetable abstract: Giving contraceptive advice antenatally is feasible and acceptable. Tweetable abstract: Giving contraceptive advice antenatally is feasible and acceptable.